Gender differences in management of patients undergoing catheter ablation of atrioventricular nodal reentry tachycardia. Issue 7 (10th June 2019) - Musa, Thaer; Darrat, Yousef; Etaee, Farshid; Butt, Muhammad; Czarapata, Melissa; McMullen, Colleen; Mattingly, Lynn; Daoud, Amro; Coy, Kevin; Ogunbayo, Gbolahan; Delisle, Brian; Elayi, Claude S.
Abstract: Background: Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common type of supraventricular tachycardia (SVT). Similar to other cardiac tests and interventions, gender bias may influence clinical decision making in providing appropriate care for AVNRT patients. We assessed for gender differences in the diagnosis and management of AVNRT patients who underwent catheter ablation. Methods: Patients who underwent catheter ablation for AVNRT were included. We explored the gender difference on various clinical parameters such as the time from SVT symptoms, SVT diagnosis, and first electrophysiology consult to time of catheter ablation. Results: Among 140 patients screened, 116 patients met the inclusion criteria, including 67.2% women. Median time from symptoms onset to SVT diagnosis was 18.5 months (interquartile range [IQR] 4.0‐58.5) in women versus 4.0 months (0.75‐34.7) in men, P  = .005. Once SVT was diagnosed, women took a median of 12.5 months (IQR 3.0‐57.0) to proceed with ablation versus 3.0 months (1.0‐7.0) for men, P  ≤ .001. It took a longer time from the first electrophysiology consultation to ablation: 54.5 days (20.75‐144.75) for women versus 20.5 days (6.0‐46.25) for men, P  = .008. Overall, it took 60.0 months (IQR 12.8‐132.0) for women to have an ablation from initial symptoms onset versus 15 months (IQR 4.6‐48.0) for men, P  = .001. Prior to ablation, women had 3.78 ± 3.79 (mean ± SD) emergency department visits for SVT versus men 1.52 ± 1.72 and women tried 1.28 ± 0.82 medications versus men 0.76 ± 0.68, P  < .001 and .001, respectively. Conclusions: This study demonstrates significant and multifactorial gender‐related disparities in AVNRT diagnosis and treatment. Larger studies are needed to confirm these results.